2009
DOI: 10.1176/ps.2009.60.12.1589
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of Mental Health Parity: Lessons From California

Abstract: Experiences in California suggest that implementation of the 2008 federal parity law should include monitoring health plan performance related to access and quality, in addition to monitoring coverage and costs; examining the breadth of diagnoses covered by health plans; and mounting a campaign to educate consumers about their insurance benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 13 publications
(7 reference statements)
0
1
0
Order By: Relevance
“…The purpose of this legislation is to increase access to care for people with mental illnesses and to eliminate inequalities in the treatment of mental and physical illnesses. A multimodal, interview based study of California's parity law, in effect since 2000, revealed that many people potentially affected by the law did not know about it and that the law had unintended consequences, including patients receiving more severe diagnoses than warranted in part because only certain diagnoses were covered by the legislation (Rosenbach, Lake, Williams, and Buck, 2009). Facets of this study could be replicated, including interviews with representative individuals potentially affected by parity legislation regarding their knowledge and understanding of the law.…”
Section: Implementation Studiesmentioning
confidence: 95%
“…The purpose of this legislation is to increase access to care for people with mental illnesses and to eliminate inequalities in the treatment of mental and physical illnesses. A multimodal, interview based study of California's parity law, in effect since 2000, revealed that many people potentially affected by the law did not know about it and that the law had unintended consequences, including patients receiving more severe diagnoses than warranted in part because only certain diagnoses were covered by the legislation (Rosenbach, Lake, Williams, and Buck, 2009). Facets of this study could be replicated, including interviews with representative individuals potentially affected by parity legislation regarding their knowledge and understanding of the law.…”
Section: Implementation Studiesmentioning
confidence: 95%